Thailand’s Low-Cost Carrier Airline Industry: Is the Services Marketing Mix the Elixir for Economic Growth and Prosperity? - Srisook, Phoom (Animo Repository, 2018)
In 2017, low-cost carrier (LCC) airlines consistently grew at a faster pace compared to the world’s average growth. In 2017, LCCs carried an estimated 1.2 billion passengers and accounted for approximately 30% of the world’s total scheduled passengers. In Southeast Asia, passenger traffic grew by approximately 10% in 2017, where six of the region’s 10 countries recorded double-digit growth. Southeast Asian airlines now have 1,600 airplanes on order, in addition to an active fleet of close to 2,000 airplanes, with LCCs currently accounting for approximately 70% of Thailand’s domestic seat capacity. Competition, however, amongst the LCCs has become fierce, with fare reductions being a common tactic to fill seats. Therefore, the researchers sought out to determine which aspects play the greatest roles in an LCC’s competitiveness, and used multi-stage random sampling to obtain 320 passenger respondents’ opinions who were departing on either Thai AirAsia, Thai Lion Air, Thai Smile, or Nok Air from one of Bangkok’s two main airports. Results determined that the service marketing mix of promotion, place, price, and services play the most important role in LCC competitiveness.